PEMBINAAN NORMA KECERGASAN FIZIKAL DALAM KALANGAN PALAPES WANITA UNIVERSITI PERTAHANAN NASIONAL MALAYSIA (UPNM) - Norfazilawati Othman (Tesis, 2020)
The six objectives of this study had been implemented with the seven types of fitness test (2.4 kilometres running, 30 meter sprint, zigzag run, sit up, bent knee push up, stand broad jump and sit and reach). The pilot study has been done in order to test the validity, reliability and objectivity or the instrument and continued with another 3 phases which involved pre-test (4 weeks), interventions (8 weeks), and post-test (4 weeks).